Metal-free annulative hydrosulfonation of propiolate esters: synthesis of 4-sulfonates of coumarins and butenolides. (24th February 2020) - Fernandes, Rodney A.; Gangani, Ashvin J.; Kunkalkar, Rupesh A.
Abstract : An efficient metal-free and cost-effective method for the synthesis of coumarin and butenolide 4-sulfonates has been developed involving addition of sulfonic acids to ethyl propiolates followed by lactonization. Abstract : An efficient metal-free and cost-effective method for the synthesis of coumarin and butenolide 4-sulfonates (46 examples) has been developed. The reaction involves addition of sulfonic acids to ethyl propiolates followed by lactonization, resulting in direct formation of coumarin and butenolide 4-sulfonates. This methodology has been elaborated to Sonogashira and Suzuki coupling including the synthesis of rac -tolterodine.